Chronic Laryngotracheal Granulomatous Disease Secondary to Sporothrix schenckii in an Immunocompromised Patient. (December 2022) - Kenny, Hannah; Dougherty, Michael; Churnin, Ian; Early, Stephen; Gupta, Akriti; McGarey, Patrick O.
Objective: To describe a rare presentation of laryngotracheal granulomatous disease secondary to sporotrichosis. Methods: The authors report a case of laryngeal sporotrichosis in an immunocompromised patient, with accompanying endoscopic images and pathology. Results/case: A 72-year-old immunocompromised female with a history of rose-handling presented with a year of hoarseness and breathy voice. Flexible nasolaryngoscopy showed diffuse nodularity; biopsy of the lesions demonstrated granulomatous inflammatory changes, and fungal culture grew Sporothrix schenkii . Long-term itraconazole treatment was initiated, with improvement in dysphonia and few residual granulomas on follow-up examination. Conclusion: When evaluating granulomatous disease of the airway, a broad differential including infectious or inflammatory etiologies should be considered, especially in immunocompromised patients. Adequate tissue samples should be collected to facilitate special staining. The current recommendations for laryngeal sporotrichosis include treatment with a prolonged course of itraconazole.